2014
DOI: 10.4161/gmic.29154
|View full text |Cite
|
Sign up to set email alerts
|

The gut flora is required for the control of intestinal infection by poly(I:C) administration in neonates

Abstract: We found that immunostimulation of the intestinal immune system of neonatal mice by poly(I:C) injection decreased intestinal infection by the parasite Cryptosporidium parvum. We showed that the presence of dendritic cells and the cooperation of mutually dependent cytokines, such as IL-12p40, and type I and type II IFNs, were involved in the mechanism of protection induced by poly(I:C). This protection is dependent not only on TLR3-TRIF signaling, but also on the activation of the TLR5-MyD88 pathway by gut micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 51 publications
(70 reference statements)
0
9
0
Order By: Relevance
“…Oral immunization with Salmonella vaccine strains has also been shown to protect against non- Salmonella bacterial infections via sustained changes in TLR expression and non-specific macrophage activation [ 75 ]. Signaling TLR3 in combination with TLR5 [ 76 , 77 ], TLR4 [ 78 ] and TLR9 [ 24 , 38 ] independently influence Cryptosporidium infection outcomes. While prior studies have focused on TLR activation immediately prior to infection, we found that even remote selective TLR activation with CpG mimicked the S .…”
Section: Discussionmentioning
confidence: 99%
“…Oral immunization with Salmonella vaccine strains has also been shown to protect against non- Salmonella bacterial infections via sustained changes in TLR expression and non-specific macrophage activation [ 75 ]. Signaling TLR3 in combination with TLR5 [ 76 , 77 ], TLR4 [ 78 ] and TLR9 [ 24 , 38 ] independently influence Cryptosporidium infection outcomes. While prior studies have focused on TLR activation immediately prior to infection, we found that even remote selective TLR activation with CpG mimicked the S .…”
Section: Discussionmentioning
confidence: 99%
“…Those authors also showed that resistance of mice to C. parvum could be increased by transferring intestinal mucosa from resistant animals to susceptible infant mice (7). A protective role of the gut microbiota against cryptosporidiosis was also observed in neonatal mice (8,9). That research found that the gut microbiota synergized with poly(I•C) to elicit protective intestinal immunity against C. parvum.…”
mentioning
confidence: 91%
“…Various Cryptosporidium species are recognized weeks [17,18]. A protective role of the gut microbiota against cryptosporidiosis was also observed in neonatal mice [19,20] A protein-deficient diet was also found to increase susceptibility of mice to C. parvum [21]. This phenotype was attributed to a reduced epithelial cell turnover.…”
Section: Introductionmentioning
confidence: 97%